THE INFLUENCE OF EXTRACURRICULAR SCOUTS OF PRASIAGA ON CHARACTER EDUCATION OF CHILDREN AGED 4-6 YEARS AT STATE KINDERGARTEN OF PEMBINA, BATU CITY - Tri Putri Syafrida; Eny Nur Aisyah; Munaisra Tri Tirtaningsih (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the influence of the Prasiaga Scout extracurricular program on the character education of children aged 4–6 years. The research employs a descriptive quantitative approach. Data were collected through observation, interviews, and questionnaires distributed to teachers and parents. The research sample consisted of 30 children who actively participated in Prasiaga Scout activities. The data analysis results indicate that children involved in the Prasiaga Scout program demonstrated positive character development. The character values observed include tolerance, responsibility, independence, discipline, cooperation, and patriotism. Therefore, the Prasiaga Scout program can be considered a relevant strategy to strengthen character education in early childhood education settings.